Unveiling Rare Hemoglobinopathies: Hematologic Characterization of Double Heterozygous Hb D and Hb E With Beta-Thalassemia—A Case Report - Aiman Mahmood Minhas; Hadia Eiman; Javed Iqbal; Ayisha Imran; A. S. Chughtai (Case Reports in Hematology, 2025)
Conclusion: Given the rising prevalence of uncommon severe hemoglobinopathies in Pakistan and existing resource limitations, targeted screening in high-risk districts and enhanced patient counseling are essential to mitigate the disease burden and improve diagnostic and management strategies.